PENDAMPINGAN PEMANFAATAN TEKNOLOGI DALAM OPTIMALISASI PROSES PENGELOLAAN PARIWISATA MELUNG - Wijaya, Anugerah Bagus; Afiana, Fiby Nur; hamdi, aulia; Rifai, Zanuar; Huberta, Bima; Al Afghani, Muhammad Akbar (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Melung Village is one of the villages that has been designated as a Tourism Village in 2022. Melung Village, which is located on the slopes of Mount Slamet with an altitude of around 800-900 meters above sea level, has a variety of village potentials, some of which include Pagubugan Melung natural tourism, organic vegetable gardens, camping ground, cultural tourism (ruwatan, lengger, and banyumasan ebeg). The proposing team and partners have agreed to determine priority issues in the implementation of community service programs, namely optimizing information technology infrastructure in the process of tourism management and services and the need to strengthen Human Resources (HR) in the use of this technology. The focus of activities in implementing this service is the implementation team working with BUM partners Alam Lestari Melung Village in developing a tourism management system and optimizing human resources in the use of digital technology to support the process of service and management of Melung village tourism. From the problems that exist, the priority objective of this activity is to contribute to solving partner problems, especially in the problem of tourism ticket management in accordance with knowledge in the field of information technology and involving internal MBKM students at AMIKOM Purwkerto University, in this activity students assist in training and mentoring and assist in application development . Of the problems that there are weaknesses and challenges, one of them is the capacity of human resources. To solve this problem, training and assistance is carried out for human resources managing BUM Desa Alam Lestari Melung in the use of technology. Training and assistance in using applications and promotional tools will be provided to partners. The implementation method used in this service is the Direct Action Method, where the steps consist of Diagnosing, Action Planning, Action Taking, Evaluating and Learning. Based on the results and discussion of the availability of a tourism management system that can be accessed through a web application that supports the process of service and management of Melung village tourism.